Analysis of Genetic Diversity in Eleven Tomato (Lycopersicon esculentum Mill.) Varieties using RAPD Markers - Tabassum, Nadra; Sony, Sonia Khan; Bhajan, Sujay Kumar; Islam, Mohammad Nurul (Plant Tissue Culture and Biotechnology, 2013)
Genetic diversity of 11 tomato (Lycopersicon esculentum Mill.) varieties was assessed through RAPD analysis. Twenty arbitrary oligonucleotide primers used in the RAPD?PCR produced a total of 584 different marker bands with an average of 29.2 bands per primer. Based on the banding pattern 94.168% polymorphism observed among the tomato varieties. Size range of amplified DNA bands varied from 0.1 ? 10 kb. A total of 15 unique bands were amplified from the genome of the 11 tomato varieties. The values of pair?wise genetic distances ranged from 0.1838 - 0.9049, indicating the presence of wide genetic diversity. The dendogram constructed based on phylogenetic relationship analysis revealed that the highest genetic diversity (0.9049) found between the variety BARI Tomato 8 and RATAN whereas the lowest (0.1838) between the variety BARI Tomato 9 and MADHURI. The dendogram has segregated the 11 tomato varieties into two major clusters. RATAN and SPECIAL?OP formed cluster 1 and rest 9 varieties viz., ROMA?VF, MARGLOBE, MADHURY and BARI Tomato 9, 2, 6, 14, 8 and 3 have constituted the second cluster. Plant Tissue Cult. & Biotech. 23(1): 49?57, 2013 (June) DOI: http://dx.doi.org/10.3329/ptcb.v23i1.15559